Umbilical cord blood transplantation from unrelated donors in patients with Philadelphia chromosome-positive acute lymphoblastic leukemia - Piñana, José Luis (Ferrata Storti Foundation, 2014)
There are very few disease-specific studies focusing on outcomes of umbilical cord blood transplantation for Philadelphia chromosome-positive acute lymphoblastic leukemia. We report the outcome of 45 patients with Philadelphia chromosome-positive acute lymphoblastic leukemia who underwent myeloablative single unit cord blood transplantation from unrelated donors within the GETH/GITMO cooperative group. Conditioning regimens were based on combinations of thiotepa, busulfan, cyclophospamide or fludarabine, and antithymocyte globulin. At the time of transplantation, 35 patients (78%) were in first complete remission, four (8%) in second complete remission and six (14%) in third or subsequent response. The cumulative incidence of myeloid engraftment was 96% at a median time of 20 days and significantly better for patients receiving higher doses of CD34(+) cells. The incidence of acute grade II–IV graft-versus-host disease was 31%, while that of overall chronic graft-versus-host disease was 53%. Treatment-related mortality was 17% at day +100 and 31% at 5 years. The 5-year relapse, event-free survival and overall survival rates were 31%, 36% and 44%, respectively. Although the event-free and overall survival rates in patients without BCR/ABL transcripts detectable at time of transplant were better than those in whom BCR/ABL transcripts were detected (46% versus 24% and 60% versus 30%, respectively) these differences were not statistically significant in the univariate analysis (P=0.07). These results demonstrate that umbilical cord blood transplantation from unrelated donors can be a curative treatment for a substantial number of patients with Philadelphia chromosome-positive acute lymphoblastic leukemia.